How effective are lead-rubber aprons in protecting radiosensitive organs from secondary ionizing radiation?. Issue 4 (November 2020) - Hayre, C.M.; Bungay, H.; Jeffery, C.
Abstract: Introduction: The purpose of this experiment was to explore the direction of scattered secondary ionizing radiation to a patient. A left lateral radiographic examination of the elbow was deemed appropriate due to its close proximity to radiosensitive organs and record dose limiting opportunities upon wearing a lead-rubber apron. Methods: An anthropomorphic phantom and lead-rubber apron (Pb 0.35 mm) was used with a 15 cc ionization chamber (model 10, 100 AT TRIAD) to measure scattered radiation to radiosensitive organs. Dose readings were recorded before and after in order to quantify dose reduction. Pearson's correlation, linear regression, t- test and one way analysis of variance (ANOVA) statistics were used to affirm how likely dose limitation was attributed to chance ( p < 0.05). Results: The lead-rubber apron offered dose reduction to most radiosensitive organs. Notably, ionizing radiation was significantly reduced to the left breast 0.0083 μGy (98%), right breast 0.0000 μGy (99.9%) and spleen 0.0262 μGy (99.9%). No empirical benefit was recorded for testes and ovaries. Interestingly, the thyroid recorded an increase in dose (0.1733 μGy; p = 0.01). This was later mitigated using a thyroid collar but identifies increased stochastic risks if lead-aprons are worn alone. Scattered radiation was also reduced to both eyes, which were not directly covered. Conclusion: Lead-rubber aprons are generally utilized to limit ionizing radiation, yet this article offers insight whereby increases to ionizing radiation to the thyroid are plausible when wearing a lead-rubber apron alone. Whilst these findings cannot be generalized to other radiographic examinations it provides insight into a potential increase risk of scatter to a radiosensitive organ. Implications for practice: This paper has implications because it identifies that lead-rubber has an impact on scattered ionizing radiation to radiosensitive organs for a lateral elbow examination. Further, it identifies the potential for ionizing radiation to be increased to the thyroid upon wearing a lead-rubber apron alone.